2019
DOI: 10.1371/journal.pone.0220777
|View full text |Cite
|
Sign up to set email alerts
|

Prevailing familial, social and cultural obstacles in keeping tobacco-free homes in urban areas of Bangladesh: A mixed-method study

Abstract: Background Millions of children and others across the world are being dangerously exposed to tobacco smoke and toxins in their own homes. Whilst there is limited interest in laws and interventions controlling tobacco use in public places in Bangladesh, no attention has been given to preventing tobacco-use inside homes. This study explores the familial and socio-cultural factors that provide obstacles for ensuring tobacco-free homes in Bangladesh. Materials and methods A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Both of these two factors were supported by another two studies from USA, and reported that parental self-abstaining from tobacco-use, This study identified that sharing tobacco products at HHs-level should not be considered as the means of hospitality. However, a study conducted in urban areas explored this perception to be significantly associated with promoting the tobacco-use at HH-level (Haque et al 2019). Such offering tobacco to guests and intimate friends who come to visit home is a traditional cultural practice in Bangladesh, and helps to continue the use of tobacco (especially SLT) products in the home environment over generations (Hasib, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both of these two factors were supported by another two studies from USA, and reported that parental self-abstaining from tobacco-use, This study identified that sharing tobacco products at HHs-level should not be considered as the means of hospitality. However, a study conducted in urban areas explored this perception to be significantly associated with promoting the tobacco-use at HH-level (Haque et al 2019). Such offering tobacco to guests and intimate friends who come to visit home is a traditional cultural practice in Bangladesh, and helps to continue the use of tobacco (especially SLT) products in the home environment over generations (Hasib, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, their knowledge and beliefs differ regarding the causation of various health effects. People of urban areas are usually more educated and knowledgeable about the consequences of tobacco use, but that does not mean, they are fully aware of the detrimental impact about tobacco-use atHHs(Haque et al 2019).…”
mentioning
confidence: 99%
“…Another study conducted in the urban areas of Bangladesh reported that SLT use is perceived as a traditional part of hospitality and is practiced widely at social gatherings such as weddings, baby shower ceremonies, religious events and other occasional festivals. 13 …”
Section: Discussionmentioning
confidence: 99%
“… 12 The use of tobacco (both smoking and SLT) is common in Bangladesh after having food, tea and snacks both in small and large social gatherings. 13–15 It has been established, however, that such traditions are harmful and detrimental to health and well-being. 13–16 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation